FAKTOR-FAKTOR PENYEBAB KETERCAPAIAN LEVEL KOGNITIF SISWA DALAM PEMECAHAN MASALAH TEOREMA PYTHAGORAS BERDASARKAN TAKSONOMI BLOOM REVISI [CONTRIBUTING FACTORS OF STUDENTS’ COGNITIVE LEVEL IN SOLVING PYTHAGOREAN THEOREM PROBLEMS FOLLOWING BLOOM’S REVISED TAXONOMY] - Rahmah, Ziaul; Darmawan, Puguh; Abdullah, Mohd Nor Syahrir (Universitas Pelita Harapan, 2024)
Eighth-grade students are expected to master the Pythagorean theorem. This understanding provides a strong foundation for various mathematical concepts. Besides, the Pythagorean theorem serves as one of the prerequisite subjects for further courses. However, these students have been reported to have low cognitive levels and encounter difficulty in learning the Pythagorean theorem. Therefore, this study explores the achievement of students' cognitive levels in solving Pythagorean theorem problems based on revised Bloom's taxonomy and the underlying factors. This research employed qualitative methods with multiple case study types. Prospective participants were 35 eighth-grade junior high school students. For the instrument, this study used semi-structured interview guidelines, written tests of problem-solving, indicator rubrics, audio-visual recording devices, and researcher notes. The data were garnered from the participants’ responses to written tests on the Pythagorean theorem, the researchers' notes, as well as the audio-visual recordings of the interviews between the researchers and the subjects. The garnered data were analyzed using techniques proposed by Miles and Huberman. The subsequent stages of the research process include data reduction, data presentation, and conclusion drawing. The findings indicate that learning experience presents a pivotal role in the achievement of higher cognitive levels. A supportive learning environment, including resources that assist in learning, can influence students' problem-solving ability to reach higher cognitive levels. Furthermore, providing various forms of problems can help hone the subject's cognitive level. Such diverse learning experiences can broaden the subject's horizons and help achieve higher cognitive levels.BAHASA INDONESIA ABSTRACT: Siswa kelas VIII diharapkan mampu untuk menguasai teorema pythagoras. Pemahaman tersebut menciptakan landasan yang kuat untuk berbagai konsep matematika dan menjadi salah satu materi pelajaran prasyarat untuk materi selanjutnya. Namun, siswa kelas VIII memiliki level kognitif rendah dan mengalami kesulitan dalam mempelajari teorema pythagoras. Tujuan penelitian ini adalah untuk menganalisis ketercapaian level kognitif siswa dalam memecahkan masalah teorema pythagoras berdasarkan taksonomi bloom revisi serta faktor penyebabnya. Penelitian ini menggunakan metode kualitatif dengan jenis studi kasus jamak. Calon subjek adalah siswa SMP kelas VIII sebanyak 35 dan terpilih 16 subjek. Instrumen yang digunakan adalah pedoman wawancara semi terstruktur, tes tertulis pemecahan masalah, rubrik indikator, alat rekam audio visual, dan catatan peneliti. Data yang digunakan adalah hasil tes tertulis subjek dalam memecahkan permasalahan teorema pythagoras, catatan peneliti, dan hasil rekaman wawancara antara peneliti dengan subjek. Penelitian ini menggunakan teknik analisis data interaktif miles dan huberman. Langkah berikutnya setelah pengumpulan data adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian adalah pengalaman belajar menjadi faktor krusial dalam ketercapaian level kognitif yang lebih tinggi. Subjek yang memiliki pengalaman belajar lebih banyak dapat mencapai level kognitif yang lebih tinggi. Lingkungan belajar yang mendukung, termasuk sumber daya yang membantu dalam belajar, dapat mempengaruhi kemampuan pemecahan masalah siswa untuk mencapai level kognitif yang lebih tinggi. Selain itu, pemberian berbagai bentuk masalah dapat membantu mengasah level kognitif subjek. Pengalaman belajar yang beragam tersebut dapat memperluas wawasan subjek dan membantu mencapai level kognitif yang lebih tinggi.